Colonialism as a Redeeming Evil in Chinua Achebe’s Things Fall Apart - Purwarno Purwarno; Andang Suhendi (Proceedings of AICS - Social Sciences, 2017)
Colonialism is commonly perceived and portrayed negatively in any discoursesand even considered as an evil. This perception is generally connected with the harsh, severe and brutal exploitation of the people and land being colonized. It is related to its historical and cultural denigration, oppression, suppression, economic exploitation and deprivation, literary prejudice and linguistic interference on the side of the colonized. However, apart from the negative impacts due to the colonialism, there is no doubt at all that ithas brought some certain positive impacts for the colonized. Colonizers have civilized huge numbers of peopleby spreading enlightenment,knowledge, information, technology, and even a love of learning all over the globe. It is while governing the indigenouspeople that theycivilizethem. This studyaims at critically studying on the colonialism as a redeeming evil in Chinua Achebe’s Things Fall Apart. It highlights the enlightenment, progress and divergent developments brought by colonialism to the Nigerian Igbo.The research result shows that colonialismhas brought some positiveimpacts and undeniable landmark achievements to the Igbo in terms of establishment of religion,building ofchurches, schools,hospitals,courts,government, trade and commerce, theacceptanceofoutcasts,thestoppageofthekilling oftwins, that have made it a necessary redeeming evil,and even a blessing in disguise.It also reveals that Chinua Achebeactually acknowledges that colonialismhas brought positive impacts to the Nigerian Igbo. The method used in thisresearch is descriptive research proposed by Kothari (2004). Keywords: Colonialism, redeeming evil, Igbo, outcast, ogbanje, osu.